Auditory discrimination: a three-variable analysis of intensity effects - Pierrel, Rosemary (1970)
The acquisition of auditory intensity discriminations in rats trained on multiple variable-interval extinction schedules was studied as a function of some of the variables that contribute to the speed of development of differential responding and the final level attained. The effects of three variables were isolated and studied in detail: (1) the decibel difference between the discriminative stimuli (intensity difference); (2) the intensity relationship between the stimuli (relative intensity); and (3) the position of the stimuli on the intensity continuum (absolute intensity). Each of the three variables generated orderly relationships and interacted with one another to produce complex effects upon differential responding.